2013
DOI: 10.1002/cta.1890
|View full text |Cite
|
Sign up to set email alerts
|

Survey of integrated‐circuit‐oscillator phase‐noise analysis

Abstract: This tutorial distills the salient phase-noise analysis concepts and key equations developed over the last 75 years relevant to integrated circuit oscillators. Oscillator phase and amplitude fluctuations have been studied since at least 1938 when Berstein solved the Fokker-Planck equations for the phase/amplitude distributions of a resonant oscillator.The principal contribution of this work is the organized, unified presentation of eclectic phase-noise analysis techniques, facilitating their application to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 199 publications
(486 reference statements)
0
28
0
Order By: Relevance
“…Therefore, v trajectory, is subject to rectification 1 Since rectification is local, it is possible(ev limit cycle of vdp oscillator, that the mappi imaging the mapping is piecewise constant. an example for quadratic ) 2 x has no dissipation term, is g equation (6) hould be noted, Ĥ , being em, is by definition a constant 2 ) changes.…”
Section: New Co-ordinate Trans Rectificamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, v trajectory, is subject to rectification 1 Since rectification is local, it is possible(ev limit cycle of vdp oscillator, that the mappi imaging the mapping is piecewise constant. an example for quadratic ) 2 x has no dissipation term, is g equation (6) hould be noted, Ĥ , being em, is by definition a constant 2 ) changes.…”
Section: New Co-ordinate Trans Rectificamentioning
confidence: 99%
“…INTRODUCTION LC/van der pol (vdp) oscillator [1]- [4] hav extensively, due to their popularity in applicatio locked loops. While simple compared to ring/rel in implementation, their phase noise are super analysis are based on linear time invariant (LTI time varying (LPTV) analysis, with nonlinearity describing function [5], [6]. Central to these concept of energy e.g.…”
mentioning
confidence: 99%
“…We consider the basis vectors u T 1 (t) = [0, 1], u T 2 (t) = [1, −1] and the covectors v T 1 (t) = [1,1], v T 2 (t) = [1,0]. It is straightforward to derive the relation between polar coordinates and the new phase-amplitude variables, in fact x = x 0 (θ) + Y (θ)R(t) implies ρ = 1 + R and ϕ = 2θ − R. Eq.s (4)-(10) can be similarly computed obtaining…”
Section: Applicationmentioning
confidence: 99%
“…As a consequence, characterizing how noise affects oscillators is crucial for practical applications. A wide variety of modeling techniques, many mainly oriented to circuit design are available: a recent and thorough review can be found in [1].…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advances in recent years, achieving low PN is still a severe challenge [1][2][3][4], especially at high frequency. Despite significant advances in recent years, achieving low PN is still a severe challenge [1][2][3][4], especially at high frequency.…”
Section: Introductionmentioning
confidence: 99%